AUTOLOGOUS STEM CELL-BASED GENE THERAPY OFFERS AN INNOVATIVE SOLUTION FOR TREATING INHERITED BLOOD CELLS DISORDERS - Faudhan, Nurul; Aisida, Yayu (Journal of Stem Cell Research and Tissue Engineering, 2024)
Recent advancements in medical treatments, particularly gene therapy using hematopoietic stem cells (HSCs), have significantly impacted the treatment of inherited blood disorders. HSCs can self-renew and differentiate into blood cells, making them essential for treating conditions like sickle cell anemia, thalassemia, and severe combined immunodeficiency (SCID). This study conducted a literature review on autologous stem cell therapy for genetic blood disorders, analyzing studies from databases such as PubMed and Scopus. Gene therapy corrects genetic defects in HSCs, offering an alternative to allogeneic transplantation by avoiding immune rejection. The therapy involves modifying stem cells in the lab, often through viral vectors or gene-editing tools, and reinfusing them into the patient to produce healthy blood cells long-term. Lentiviral vectors, considered safer than retroviruses, have been particularly effective in treating various conditions, including immunodeficiencies and hemoglobinopathies. The ex vivo gene transfer approach, commonly used for genetic disorders, has shown promise for one-time curative treatments, especially for pediatric diseases. However, early gene therapy efforts, such as the use of gamma-retroviral vectors for SCID, faced complications like leukemia, leading to a shift towards safer lentiviral vectors. Despite its complexity, the procedure has a low failure rate and provides a less risky alternative to traditional allogeneic stem cell transplants. Ultimately, HSC gene therapy holds significant potential for curing genetic blood disorders by permanently altering the stem cells, ensuring long-term benefits and improved treatment outcomes, with ongoing advancements in safety and efficacy.